Enhancement of glucose production from sugarcane bagasse through an HCl-catalyzed ethylene glycol pretreatment and Tween 80. (July 2022) - Lv, Yanting; Chen, Zhengyu; Wang, Huan; Xiao, Yongcang; Ling, Rongxin; Gong, Murong; Wei, Weiqi
Abstract: In this work, an HCl-catalyzed ethylene glycol (EG) pretreatment was exploited for promoting sugar release from sugarcane bagasse (SCB). The results showed that the combination of HCl and EG could remove the xylan (∼100.0%) and lignin (∼61.3%) in SCB together, which finally resulted in the pretreated substrate having a good efficacy for follow-up enzymatic hydrolysis. The maximum glucose yield of this work was 93.9% and obtained after pretreatment at 130 °C for 60 min with 0.5% HCl and 72 h enzymatic digestion. The analysis of various pretreated or un-pretreated SCB indicated that the changes of surface morphology and internal compositions of SCB were the mainly reasons for its hydrolysis efficiency enhancement. The addition of Tween 80 into hydrolysis process could remarkably shorten hydrolysis time and cellulase dosage from 72 h to 36 h and 20 FPU/g substrate to 10 FPU/g substrate, respectively, meanwhile maintaining a relatively high glucose yield (91.4%).